2006
DOI: 10.1289/ehp.8056
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality Influences Reproduction in Female Mosquitofish ( Gambusia holbrooki ) from Eight Florida Springs

Abstract: Contamination of freshwater ecosystems with nitrate is a growing global concern. Although nitrate pollution is recognized as a cause of aquatic eutrophication, few studies have examined the possible physiological impacts of nitrate exposure. In this study, we surveyed several reproductive variables of viviparous female Gambusia holbrooki (Poeciliidae) captured from eight springs in Florida. The eight springs represent a gradient of nitrate contamination (1–5 mg/L nitrate–nitrogen). We had two objectives in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 38 publications
0
38
0
Order By: Relevance
“…While all water quality variables measured in this study have been shown to affect reproductive characteristics of poeciliids (Rubin, 1985;Edwards et al, 2006), one of the most important is temperature. Indirectly, the temperature patterns observed in CNP can work in conjunction with longitudinally increasing nutrient input and insolation to influence productivity.…”
Section: Discussionmentioning
confidence: 84%
“…While all water quality variables measured in this study have been shown to affect reproductive characteristics of poeciliids (Rubin, 1985;Edwards et al, 2006), one of the most important is temperature. Indirectly, the temperature patterns observed in CNP can work in conjunction with longitudinally increasing nutrient input and insolation to influence productivity.…”
Section: Discussionmentioning
confidence: 84%
“…Similar to the mammalian penis, the gonopodium in mosquitofish develops under the control of androgens [Edwards and Guillette 2007]. In female mosquitofish, nitrate was negatively associated with embryo weight and rate of productivity [Edwards et al 2006]. Although mechanisms were not established, investigators theorized that reduced embryo weights and productivity rates were due to nitrate altered thyroid function, which has been demonstrated in other fish and mammals [Jahreis et al 1991;Allen et al 1996;Crow et al 1998;Zaki et al 2004].…”
Section: Environmental Nitrate and Reproductive Dysfunctionmentioning
confidence: 99%
“…As mentioned, the presence of xenobiotics in the water and the great variability of chemicals resulting from anthropogenic activities modify the reproduction of fish and other aquatic organisms in various ways (Edwards et al, 2006;Edwards and Guillette, 2007;Wu, 2009;Prado et al, 2011;Hued et al, 2013). Many effects of pollutants, such as the reduction in GSI and the inhibition of ovarian growth, can be attributed to changes in steroidogenesis (Kime, .…”
Section: Hormonal and Metabolic Adjustmentmentioning
confidence: 99%